2013
DOI: 10.1186/1475-2891-12-78
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kivia powder on Gut health in patients with occasional constipation: a randomized, double-blind, placebo-controlled study

Abstract: ObjectiveTo evaluate the efficacy of Kivia powder on supporting overall gut health through the relief of the discomfort of occasional constipation.DesignRandomized, double-blind, placebo-controlled, parallel-group trial.InterventionsThe investigational product for this study was Kivia powder (Vital Food Processors Ltd., Auckland, New Zealand), containing the active ingredient Zyactinase™, 5.5 g taken daily for four weeks.ResultsOne hundred thirty-eight subjects reporting occasional constipation were screened a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 17 publications
2
54
0
Order By: Relevance
“…The remaining three reports were excluded 18,19,21. Four studies were further excluded because they enrolled subjects with other conditions, for example, allergic diseases and constipation 2225. Finally, five randomized controlled trials met the inclusion criteria and were included in this systematic review and meta-analysis 20,26–29.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining three reports were excluded 18,19,21. Four studies were further excluded because they enrolled subjects with other conditions, for example, allergic diseases and constipation 2225. Finally, five randomized controlled trials met the inclusion criteria and were included in this systematic review and meta-analysis 20,26–29.…”
Section: Resultsmentioning
confidence: 99%
“…These effects may be helpful for dyslipidemic patients. In addition, kiwifruit was reported to have beneficial effects in patients with constipation problem25 and neuropathic diabetic foot ulcer 38. One study, being a nonrandomized trial and therefore not included in our systematic review, demonstrated that consumption of two kiwifruits per day for 8 weeks could improve HDL and decrease LDL/ HDL ratio and TC/HDL ratio in hyperlipidemic subjects 9…”
Section: Discussionmentioning
confidence: 99%
“…The effect is largely attributed to the soluble fibre content of the fruit, which has a high water-holding capacity (ability to incorporate water into the fibre matrix), and high viscosity that helps with faecal bulking and softening ( 14 ) . Further digestive health efficacy may also be related to the activity of actinidin, a proteolytic enzyme that may produce laxative effects, and a high polyphenol content that may also confer further health benefits ( 15 ) . Previous clinical trials investigating the performance of ‘Hayward’ kiwifruit in healthy individuals as well as in older persons, constipated and IBS-C populations showed significant improvements relating to digestive health, including increased faecal frequency and reductions in bowel transit times as well as positive changes in overall wellbeing ( 16 18 ) .…”
mentioning
confidence: 99%
“…Constipation is one of the most common digestive tract diseases in clinic [31]. Its main symptoms are prolonged defecation cycle, fewer numbers of feces, and disappearance of defecation intention [32]. At the same time, abdominal distension, mental fatigue, reduced body mass, dark complexion, and other symptoms such as irritability, bad breath, Figure 2: YTC shorten the defecating time of first black feces and improved the carbon propulsion rate in diphenoxylate-induced constipation mice.…”
Section: Discussionmentioning
confidence: 99%